2011
DOI: 10.1177/0731684411416267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of types of fillers and filler loading on the properties of silicone rubber composites

Abstract: In this study, the effects of loading levels of nano BN, nano SN and synthetic ND particles on the thermal and mechanical properties of silicone rubber were investigated. Nanoparticle-filled silicone rubber composites were prepared by cast molding process. In general, incorporation of thermally conductive nanoparticles to the silicone rubber matrix improved the thermal conductivity of the composites. BN particles have the most pronounced effect on the thermal conductivity in comparison to SN and ND particles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 21 publications
5
24
0
Order By: Relevance
“…A small increase in the peak melting temperature is observed upon addition of filler which reflects the restriction in polymer chain segmental motion during the melt as would be expected for materials with a strong polymer-filler type interaction (Fig 9). The thermal conductivity of our samples is consistent with similar materials reported in the literature and indicates the insitu modification of BN does not affect the thermal properties [10,11]. The incorporation of h-BN led to a reduction in the thermal expansion as expected (Fig 15), however, no …”
Section: Thermal Properties Of Composite Materialssupporting
confidence: 93%
See 2 more Smart Citations
“…A small increase in the peak melting temperature is observed upon addition of filler which reflects the restriction in polymer chain segmental motion during the melt as would be expected for materials with a strong polymer-filler type interaction (Fig 9). The thermal conductivity of our samples is consistent with similar materials reported in the literature and indicates the insitu modification of BN does not affect the thermal properties [10,11]. The incorporation of h-BN led to a reduction in the thermal expansion as expected (Fig 15), however, no …”
Section: Thermal Properties Of Composite Materialssupporting
confidence: 93%
“…BNPoly(dimethylsiloxane) (BN-PDMS) composite materials reported in the literature show that the incorporation of h-BN leads to an increase in the tensile modulus with a subsequent reduction in the tensile strength and strain at break when compared to the unfilled host matrix. This is suggested to be due to poor interfacial interaction/lack of particle-matrix adhesion in addition to poor dispersion of filler and inclusion of voids in these materials [11,10]. However, the nature of the interaction between h-BN and PDMS networks was not investigated.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
See 1 more Smart Citation
“…This may be due to the high specific surface area of nano-TiO 2 , which is likely to reinforce the contact area and the 18 Studies show that the interaction between the fine particulate filler and matrix can increase the elongation at break of the filling system. 19 However, the concentration of nanoparticles in silicone elastomers at 4% and 6% exhibited a certain degree of agglomeration, in which the molecular chains were fixed more firmly around the nanoparticles, weakening the interaction with the silicone elastomer. 20 Kulik et al 21 and Chatterjee 22 suggested that the high modulus characteristics of nanoparticles can decrease the elastic modulus of the filling material.…”
Section: Tensile and Tear Propertiesmentioning
confidence: 99%
“…Microsized and nanosized thermally conductive fillers, such as graphite [185], graphene [105,186,187], CNTs [136,188,189], BN [190,191], ZnO [192], and diamond [193], have been incorporated into rubber. The thermal conductivities of the typical fillers are summarized in Table 1.…”
Section: Filler Types Sizes and Aspect Ratiosmentioning
confidence: 99%